Success in pharmaceutical research: The changing role of scale and scope economies, spillovers and competition - Tatiana Plotnikova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper investigates the determinants of success in the development of new drugs. In specific, it explores the factors of success in drug development programs at different stages of innovation process. We use economies of scale, scope, R&D competition and technological spillovers as explanatory variables and test whether the effect of these variables on the success of a project differs in relation to the discovery and development stages of innovation, respectively. Our main finding is that spillovers, including spillovers from collaboration, are important in explaining the success of projects during the discovery stage of innovation, while in the later development stage, the effects of competition outweigh any benefits from spillovers.
Keywords: O32; L25; L65; 330; economies of scale and scope; spillovers; competition; R&D; innovation process; Pharmazeutische Forschung; Innovation; Erfolgsfaktor; Verbundvorteil; Skalenertrag; Innovationswettbewerb; Wissenstransfer; Spillover-Effekt; Schätzung; Welt